2017
DOI: 10.1186/s13071-017-2464-2
|View full text |Cite
|
Sign up to set email alerts
|

High seroprevalance of Neospora caninum in dogs in Victoria, Australia, compared to 20 years ago

Abstract: BackgroundCanids are definitive hosts of the apicomplexan parasite Neospora caninum, the leading cause of abortion in cattle worldwide. For horizontal transmission from canids to occur, oocysts of N. caninum must be shed by the definitive host into the environment of susceptible intermediate hosts such as cattle. The purpose of this study was to determine the prevalence of N. caninum in canids in Victoria, Australia’s leading dairy producing state.Results Neospora-like oocysts were observed in 8% (18/234) of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
(59 reference statements)
0
10
1
2
Order By: Relevance
“…(1997) . We could not confirm the hypothesised increase in the N. caninum seroprevalence in Sydney, New South Wales, since 1997, based on a six-fold increase in N. caninum seroprevalence recently demonstrated for dogs in Melbourne, Victoria ( Sloan et al., 2017 ). The knowledge of the seroprevalence is of equal value when treating animals with immunosuppressive drugs which is common for a wide variety of non-neosporosis related canine diseases.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…(1997) . We could not confirm the hypothesised increase in the N. caninum seroprevalence in Sydney, New South Wales, since 1997, based on a six-fold increase in N. caninum seroprevalence recently demonstrated for dogs in Melbourne, Victoria ( Sloan et al., 2017 ). The knowledge of the seroprevalence is of equal value when treating animals with immunosuppressive drugs which is common for a wide variety of non-neosporosis related canine diseases.…”
Section: Discussioncontrasting
confidence: 59%
“…Seroprevalence of anti- N. caninum IgG was established for domestic dogs in Melbourne, Perth and Sydney in 1997 ( Barber et al., 1997 ). Seroprevalence in Melbourne was recently demonstrated to increase from 5% in 1997 to 34% in 2017 ( Sloan et al., 2017 ). This rise in seroprevalence means a higher proportion of dogs at risk of developing adult-onset canine neosporosis as a consequence of recrudescence of N. caninum .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of active infection with Cryptococcus , Neospora , and Toxoplasma in this population is unknown. The seroprevalence of N. caninum in dogs sampled across Victoria in 2017 was ~30% (29.8% using cELISA and 32.9% using IFAT) indicating that many dogs in this region may have been exposed 39 . Faecal oocyst shedding was not detected and no dogs in the aforementioned study were reported to have any clinical signs suggestive of active infection with N. caninum 39 .…”
Section: Discussionmentioning
confidence: 81%
“…The seroprevalence of N. caninum in dogs sampled across Victoria in 2017 was ~30% (29.8% using cELISA and 32.9% using IFAT) indicating that many dogs in this region may have been exposed 39 . Faecal oocyst shedding was not detected and no dogs in the aforementioned study were reported to have any clinical signs suggestive of active infection with N. caninum 39 . A recent study looking at the prevalence of protozoal infection in suspected MUO cases in the UK reported an exposure prevalence of 3.98% and 6.96% for T. gondii and N. caninum respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto a la seropositividad de acuerdo con la edad, la mayor positividad fue observada en los animales jóvenes (40%) que coincide con los datos reportados, en perros de Victoria, Australia, sin embargo en el grupo de adultos se encontró la mayor prevalencia (28). La raza, sexo y edad, no fueron factores asociados a la seroprevalencia , como se observó en caninos del área central de China (23).…”
Section: Resultsunclassified